ANALISIS BAGI HASIL FINANCING DALAM PERBANKAN SYARIAH - Aswad, Muhammad (IAIN Tulungagung, 2014)
Islamic banking function as intermediaries from surplus units to units depisit, Islamic banks as well as the unit of funding (fundraising) also function in fnancing (fnancing). In the application of Islamic banking operations face technical constraints associated with the sharing system (Proft and Loss Sharing), therefore Islamic banking fnancial intermediary, in this case the Islamic banks are not just trying to maximize the expected utility of its shareholders, but also pay attention to expected utility entrepreneurs and depositors. In Islamic banking operations apply for the results as a measure of return in the economy. Penentua technically specifed ratio is fxed at the beginning of the transaction but the nominal value can not be known with certainty, but see the income that will happen later. In determining the ratio ratio known as 1) Revenue sharing system; 2) Groos Proft System; and 3) Proft Sharing System. But with the objective conditions of our economy now Revenue Sharing System.Keywords: Islamic Banking, Proft Sharing Sytem Revenue sharing, Groos Proft System.